COVID-19 Prevention Behavior on Online Transportation Drivers in Samarinda, Indonesia - Muhammad Sultan (Universitas Airlangga, 2021)
Introduction: The numbers of COVID-19 sufferers in various countries are continuing to increase, including in Indonesia. COVID-19 has a wide impact, including on the online transportation service sector. Since 2015 in Samarinda City, there has been an online transportation service, namely Gojek Indonesia, which provides services to customers in the form of shuttle passengers, food delivery, and other necessities, including goods delivery services. The online transportation driver group is one of the groups at high risk of transmitting COVID-19. Objective: This study aimed to obtain information about COVID-19 prevention behavior including driver's knowledge of COVID-19, perceptions, and customer service on online transportation drivers in Samarinda. Methods: This study used a qualitative design with a phenomenological approach. The informants in this study were selected as many as 5 people. The Gojek at Cendana Street was chosen because it is the main entrance and exit route of tourists in Samarinda. The data technique was an interview and used qualitative data analysis. Results: COVID-19 is a respiratory disease. Drivers considered that COVID-19 is a dangerous disease, frightening, and causes excessive panic in the community because of its rapid spread and risks to all groups of people, including online transportation drivers. Serving customers remains a priority even though they understand the risk of contracting COVID-19. Efforts to prevent the transmission of COVID-19 carried out by Gojek drivers including using masks, washing hands with flowing water and soap, or hand sanitizer, also cleaning helmets or replacing them with spare helmets. Conclusion: The transmission of COVID-19 can be prevented by behaving cleanly and healthy also prioritize the prevention of transmission of COVID-19, such as wearing masks while doing activities, keeping passenger helmets clean, and washing hands after serving customers.